The Effect of Service Quality, Physical Environment, and Medical Staff Kindness & Consideration on Patient Loyalty with Patient Satisfaction as a Mediating Variable in General Hospitals in Serui - Stephanie Caroline; Yohana Cahya F. Palupi Meilani (Journal of Social Research, 2025)
This study aims to analyze the impact of Service Quality, Physical Environment, and Medical Staff Kindness & Consideration on Patient Loyalty with Patient Satisfaction as a mediating variable at the General Hospital of Serui (RSUD Serui). The study employs a quantitative approach with a sample of 160 patients selected through purposive sampling. Data were analyzed using PLS-SEM. The results indicate that Service Quality, Medical Staff Kindness & Consideration, and Physical Environment have a positive and significant effect on Patient Satisfaction. Furthermore, Patient Satisfaction mediates the relationship between these variables and Patient Loyalty. Specifically, improvements in service quality, the friendly and attentive behavior of medical staff, and a comfortable and clean physical environment significantly contribute to enhancing patient satisfaction, which in turn strengthens their loyalty to the hospital. The implications of this study suggest that RSUD Serui should focus on improving service quality, providing communication and empathy training for medical staff, and enhancing physical facilities to create a positive patient experience. This study provides strategic insights for the management of RSUD Serui to strengthen patient loyalty through satisfaction derived from service quality, physical environment, and positive staff interactions. Managerial implications from this study indicate that the management of RSUD Serui should pay more attention to improving service quality, the comfort of facilities, and the empathy of medical staff to increase patient satisfaction and loyalty. Training in communication and empathy for medical staff, improving ventilation systems and cleanliness of facilities, and utilizing technology for administrative efficiency are strategic steps that can strengthen long-term relationships with patients.